Diferenças de sexo nos fatores de risco para fragilidade em idosos e na sua relação com incapacidade funcional: uma análise de trajetórias - Oliveira, Dayane Capra de (2021)
The mechanism, the risk factors and the influence of sex on the incidence of frailty components are not completely known. In addition, the relationship between frailty and disability has been explored in a two-way street with studies showing that the frailty process increases the risk of disability and that disability increases the risk of frailty. However, there is a gap in the literature, as far as is known, no stratified analyzes by sex of the risk factors for the incidence trajectory of the number of frailty components as well as for the behavior of the functional disability trajectories in function changes in frailty status and their components over time. Therefore, in order to establish efficient rehabilitation programs for frail or in process of becoming frail older people, these knowledge gaps need to be filled. This thesis has two objectives: 1) To analyze sex differences in risk factors for the increase in the number of frailty components in 1,747 participants in the ELSA Study followed for twelve years; and 2) Analyze sex differences in the trajectories of the incidence of disability due to changes in frailty status and their components in 1,522 and 1,548 participants in the ELSA Study independent in ABVD and IADL and frailty at baseline also in a twelve-year follow-up. The main results found were that the increase in the number of frailty components, in both sexes, was associated with increasing age, low education, perception of poor vision, presence of depressive symptoms, joint disease, uncontrolled diabetes, C-reactive protein high and sedentary lifestyle (p <0.05). In men, the presence of osteoporosis, low weight, heart disease, living with one or more people and perception of poor hearing were associated with an increase in the number of components of frailty (p <0.05). In women, the increase in fibrinogen, controlled diabetes, stroke and the perception of regular vision were associated with an increase in the number of components of frailty (p <0.05). Obese women and men and overweight women showed a smaller increase in the number of components compared to the eutrophic. It was also found that women who became pre-frail and men and women who became frail had worse trajectories of incidence of disability (p < 0.05) than those who remained non-frail during the follow-up period. Slowness was the only component of frailty capable of discriminating the incidence of disability regarding BADL and IADL in both sexes (p < 0.05). In addition to slowness, weakness and low physical activity level (BNAF) also discriminated against the incidence of disability in men while exhaustion discriminated against women (p <0.05). However, we understand that although there are similarities in the factors associated with the trajectory of increasing the number of frailty components between the sexes, socioeconomic factors, low weight and musculoskeletal and cardiac alterations determined the frailty process in men while cardiovascular and neuroendocrine alterations determined the frailty process in women. Furthermore, slowness as a component and not frailty as a construct, seems to us to better signal the process of disability in the older people. Therefore, as its evaluation is easy, fast and accessible, screening for this frailty component should be prioritized in different clinical contexts so that rehabilitation strategies can be developed to avoid the onset of disability.